Internal Control and Standard Operating Procedures in Malaysian Corporations - Nadianatra, Musa; Clift, Bob (UTeM, 2017)
—The security, standards, and related controls of IT/IS infrastructure along with its implementation in Malaysian Corporation has been the main focus of the study. A cross sectional analysis has been implemented, using the qualitative research design, to evaluate the importance of internal control and standard operating procedures. The interview data, website analysis, and mail surveys have been collected concerning the perfection of boards and senior management about the IS/IT security processes. Both the senior and board management are ought to be responsible and accountable to ensure that IS/IT risks are addressed in the standards and policies of IS/IT security. Success and failure of development are also the responsibility of boards and senior management. IT/IS procedures must be implemented by corporation to control the risk related with the use of operation and information systems that supports the mission of business.